A theoretical framework for the ecological role of three‐dimensional structural diversity. Issue 1 (1st February 2023) - LaRue, Elizabeth A; Fahey, Robert T; Alveshere, Brandon C; Atkins, Jeff W; Bhatt, Parth; Buma, Brian; Chen, Anping; Cousins, Stella; Elliott, Jessica M; Elmore, Andrew J; Hakkenberg, Christopher R; Hardiman, Brady S; et al.
Abstract : The three‐dimensional (3D) physical aspects of ecosystems are intrinsically linked to ecological processes. Here, we describe structural diversity as the volumetric capacity, physical arrangement, and identity/traits of biotic components in an ecosystem. Despite being recognized in earlier ecological studies, structural diversity has been largely overlooked due to an absence of not only a theoretical foundation but also effective measurement tools. We present a framework for conceptualizing structural diversity and suggest how to facilitate its broader incorporation into ecological theory and practice. We also discuss how the interplay of genetic and environmental factors underpin structural diversity, allowing for a potentially unique synthetic approach to explain ecosystem function. A practical approach is then proposed in which scientists can test the ecological role of structural diversity at biotic–environmental interfaces, along with examples of structural diversity research and future directions for integrating structural diversity into ecological theory and management across scales.